2019
DOI: 10.15586/jkcvhl.2019.115
|View full text |Cite
|
Sign up to set email alerts
|

Trifecta Outcomes in Open, Laparoscopy or Robotic Partial Nephrectomy: Does the Surgical Approach Matter?

Abstract: This retrospective study evaluated perioperative outcomes of open partial nephrectomy (OPN), laparoscopic partial nephrectomy (LPN), and robot-assisted partial nephrectomy (RAPN) and identified predictive factors of Trifecta achievement for renal tumors that underwent partial nephrectomy (PN) in a single institutional cohort. The study involved patients who underwent PN from January 2011 to July 2018. Trifecta was defined as absence of perioperative complications, no positive surgical margins, and ischemia tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…As in our study, Mehra et al [16] found that blood loss was lowest in the RAPN group (OPN > LPN > RAPN, p = 0.042). This can be explained by better visualization of the anatomy and movement control of instruments in RAPN.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As in our study, Mehra et al [16] found that blood loss was lowest in the RAPN group (OPN > LPN > RAPN, p = 0.042). This can be explained by better visualization of the anatomy and movement control of instruments in RAPN.…”
Section: Discussionsupporting
confidence: 83%
“…As in our study, Mehra et al [16] found that the operative time was not different among the three groups.…”
Section: Discussionsupporting
confidence: 77%
“…In this context, the concepts of trifecta and pentafecta, which are commonly used to evaluate the outcomes of LPN, are utilized. Although there are several different definitions for trifecta in the literature, the main goals of the trifecta outcomes in terms of LPN are achieving negative surgical margin, minimizing postoperative complications and WIT (22). Besides the definition of a diverse trifecta criterion, the characteristics of the patients and the tumor included in the studies, the surgical technique used and the surgical experience might have resulted in reporting disparate success rates (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Over time, however trifecta outcomes have shown a wide range of variation not only because of normal differences in surgical expertise and volume, but also because many changes have been made to the original definition. This entirely affects the comparison of success across the contemporary series with some studies, including a warm ischemia time (WIT) ranging over 25 min or 30 min, complications over Clavien 2 or 3, or reductions up to 30% in postoperative eGFR [ 4 , 5 ]. Another important effort in standardization is the development of nephrometry scores, which aim to objectively classify the complexity of a renal mass and to predict the possibility of postoperative complications.…”
Section: Pn In Complex Scenariosmentioning
confidence: 99%